PENTINGNYA EVALUASI AFEKTIF PADA PEMBELAJARAN PAI DI SEKOLAH - Betwan, Betwan (Universitas Islam Sultan Agung, 2019)
ABSTRACTAffective evaluation is one of the evaluation types in PAI learning. However, problems found in the field, that teachers tend to ignore affective evaluation and focus more on learning on cognitive completion alone. So that a gap emerges, the values listed on the student's affective column are not necessarily in accordance with student behavior. So the problem in this study is how to implement affective evaluations of students in Sultan Agung Islamic Junior High School 4 Semarang in PAI learning.This research is a field research with a qualitative descriptive approach. The subject of this study were the principal, PAI teacher, and students of Sultan Agung Islamic Junior High School 4 Semarang. While the object of research is the affective evaluation of PAI learning with researchers as a key instrument in research. Data in the study were collected using observation and interview techniques to obtain primary data and documentation to obtain secondary data. In the process of collecting data, researchers always make field notes so that the data obtained is not forgotten and can be accurate data. Increasing the persistence of observation, triangulation, and analyzing the negative case, and member check is the technique used to test data credibility. Furthermore, the data are analyzed by steps: analyzing the data that has been collected, conducting data reduction, arranging data, checking the validity of the data, interpreting the data, and concluding the results of the research inductively.The results showed that the implementation of affective evaluations of students at Sultan Agung Islamic Junior High School 4 Semarang had not been done effectively. This is because the teacher has not prepared a good affective evaluation plan and in its implementation is not yet in accordance with what is stated in the planning. The teacher only uses daily observations and observations without using observation sheets in conducting evaluations. Keywords: Affective Evaluation, PAI Learning